Efektivitas Media Sosial Instagram sebagai Media Promosi Gamis Syar’i - Evianah Evianah; Dwi Indah Mustikorini; Wiwik Herawati (CiDEA Journal, 2024)
Promotional activities via social media such as Instagram are a form of marketing communication mix that is directly related to the level of consumer exposure until consumers make the decision to buy this syar'i gamis product. The demographic diversity of consumer characteristics also greatly influences the effectiveness of promotions via social media. The aim of this research is firstly to analyze the effectiveness of promotion of Islamic gamis via Instagram, secondly to find out how big the relationship is between follower characteristics and effectiveness of promotion via Instagram of Islamic gamis products and thirdly to find out consumer responses regarding the use of promotional syar'i gamis products. 'i via social media Instagram.The results of this research are that promotions carried out via Instagram are quite good. Promotion of syar'i gamis through social media Instagram is very effective in stimulating attention, increasing respondents' knowledge of the products being marketed, generating interest in followers, generating desire and ultimately making followers buy syar'i gamis products and then recommending them to other people.